Model Reference Command Shaping For Vibration Control Of Multimode Flexible Systems With Application To A Double-pendulum Overhead Crane - H.I. Jaafar,; Z. Mohamed,; M.A. Shamsudin,; N.A. Mohd Subha,; Liyana Ramli; A.M. Abdullahi (Elsevier, 2024)
Indexed by SCOPUS/ERA